2020
DOI: 10.1002/oby.22811
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Regulation of Peripheral Glucose Metabolism: Potential Effects of Exercise Timing

Abstract: Diurnal oscillations in energy metabolism are linked to the activity of biological clocks and contribute to whole‐body glucose homeostasis. Postprandially, skeletal muscle takes up approximately 80% of circulatory glucose and hence is a key organ in maintenance of glucose homeostasis. Dysregulation of molecular clock components in skeletal muscle disrupts whole‐body glucose homeostasis. Next to light‐dark cycles, nonphotic cues such as nutrient intake and physical activity are also potent cues to (re)set (dys)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 83 publications
0
13
0
1
Order By: Relevance
“…Similarly, Mancilla et al reported that afternoon exercise may help improve adipose tissue insulin-sensitivity to a larger extent than morning exercise, which would mean a greater free-fatty acid suppression capacity during the afternoon period in the insulin-stimulated state, hence contributing to a decrease in ectopic fat accumulation. 4,12 Nonetheless, morning exercise has been associated with more consistent adherence, decreased daily energy intake, and higher total daily MVPA 13 compared with that performed at other times of the day, which can lead to a greater body weight loss. It is important to note that any MVPA is better than none and it should still be stressed that the best time for individuals with type 2 diabetes to be physically active is when they are able and motivated to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Mancilla et al reported that afternoon exercise may help improve adipose tissue insulin-sensitivity to a larger extent than morning exercise, which would mean a greater free-fatty acid suppression capacity during the afternoon period in the insulin-stimulated state, hence contributing to a decrease in ectopic fat accumulation. 4,12 Nonetheless, morning exercise has been associated with more consistent adherence, decreased daily energy intake, and higher total daily MVPA 13 compared with that performed at other times of the day, which can lead to a greater body weight loss. It is important to note that any MVPA is better than none and it should still be stressed that the best time for individuals with type 2 diabetes to be physically active is when they are able and motivated to do so.…”
Section: Discussionmentioning
confidence: 99%
“…esercizio isometrico, con pesi) è la forma di esercizio più suscettibile alle variazioni diurne, con il picco di forza muscolare tipicamente osservato tra il pomeriggio e la sera (16:00-20:00) e i valori minimi al mattino (06:00-10:00). Analogo pattern diurno è stato riportato per l'esercizio ad alta intensità [13]. La termoregolazione e le sue variazioni circadiane rappresentano una modalità indiretta attraverso la quale il nucleo soprachiasmatico influenza la risposta circadiana nel muscolo scheletrico e, indirettamente, l'efficienza della risposta all'esercizio fisico.…”
Section: Esercizio Fisico E Ritmi Circadianiunclassified
“…In mice it was shown that muscle contractions, as part of exercise, are sufficient to shift the muscle circadian clock phase [35]. Since nutrition is an important zeitgeber as well, it was recently suggested that there might be an optimal time for exercise in relation to meal timing for maximal improvement of muscle and whole body insulin sensitivity and glucose homeostasis [36]. Applying circadian principles to exercise interventions is thus considered to hold potential for improving exercise outcomes not only for patients, but also for healthy subjects and even elite athletes [37].…”
Section: Feeding and Exercise As Important Cues For Diurnal Entrainmentmentioning
confidence: 99%